The unequal distribution of water risks and adaptation benefits in coastal Bangladesh - Barbour, EJ; Adnan, MSG; Borgomeo, E; Paprocki, K; Khan, MSA; Salehin, M; Hall, JW (Springer Nature, 2022)
Increasing flood risk, salinization and waterlogging threaten the lives and livelihoods of more than 35 million people in Bangladesh’s coastal zone. While planning models have long been used to inform investments in water infrastructure, they frequently overlook interacting risks, impacts on the poor and local context. We address this gap by developing and applying a stochastic-optimization model to simulate the impact of flood embankment investments on the distribution of agricultural incomes across income groups for six diverse polders (embanked areas) in coastal Bangladesh. Results show that increasing salinity and waterlogging negate the benefits of embankment rehabilitation in improving agricultural production while improved drainage can alleviate these impacts. Outcomes vary across income groups, with risks of crop loss being greatest for the poor. We discuss the need for planning models to consider the interacting benefits and risks of infrastructure investments within a local political economy to better inform coastal adaptation decisions.